2017
DOI: 10.1109/tnsre.2016.2546062
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying Smartphone Screen Using Google Glass for Low-Vision Users

Abstract: Magnification is a key accessibility feature used by low-vision smartphone users. However, small screen size can lead to loss of context and make interaction with magnified displays challenging. We hypothesize that controlling the viewport with head motion can be natural and help in gaining access to magnified displays. We implement this idea using a Google Glass that displays the magnified smartphone screenshots received in real time via Bluetooth. Instead of navigating with touch gestures on the magnified sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…In total, 40 studies were conducted in the United States [ 6 - 9 , 13 - 18 , 20 - 24 , 27 , 29 , 31 , 32 , 35 , 37 - 41 , 43 - 52 , 54 - 57 ], three in Germany [ 25 , 26 , 53 ], two in United Kingdom [ 10 , 11 ], China [ 34 , 36 ], and one each in Australia [ 33 ], Switzerland [ 42 ], Mexico [ 19 ], Netherlands [ 12 ], Norway [ 30 ], and Italy [ 28 ]. Less than half of the included studies (19/51, 37%) were conducted in a laboratory setting [ 6 - 9 , 12 , 14 , 16 - 19 , 21 - 24 , 27 , 31 , 33 , 42 , 50 ], 13 (25%) in a hospital setting [ 32 , 34 , 36 , 38 , 39 , 43 , 44 , 46 , 51 , 53 - 56 ], seven (14%) in a classroom or clinical student training setting [ 35 , 37 , 40 , 41 , 47 , 48 , 52 ], three in patient residences (6%) [ 13 , 15 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 40 studies were conducted in the United States [ 6 - 9 , 13 - 18 , 20 - 24 , 27 , 29 , 31 , 32 , 35 , 37 - 41 , 43 - 52 , 54 - 57 ], three in Germany [ 25 , 26 , 53 ], two in United Kingdom [ 10 , 11 ], China [ 34 , 36 ], and one each in Australia [ 33 ], Switzerland [ 42 ], Mexico [ 19 ], Netherlands [ 12 ], Norway [ 30 ], and Italy [ 28 ]. Less than half of the included studies (19/51, 37%) were conducted in a laboratory setting [ 6 - 9 , 12 , 14 , 16 - 19 , 21 - 24 , 27 , 31 , 33 , 42 , 50 ], 13 (25%) in a hospital setting [ 32 , 34 , 36 , 38 , 39 , 43 , 44 , 46 , 51 , 53 - 56 ], seven (14%) in a classroom or clinical student training setting [ 35 , 37 , 40 , 41 , 47 , 48 , 52 ], three in patient residences (6%) [ 13 , 15 ,…”
Section: Resultsmentioning
confidence: 99%
“…Most (n=38) did not report any specific age information for participants [ 7 , 8 , 13 - 15 , 19 - 21 , 26 - 52 , 54 - 56 ], but none of these were conducted in pediatric settings. Of the 13 studies that did report participant age information, seven enrolled young adults (average age or age range ≤35 years) [ 6 , 18 , 22 - 25 , 53 ], three enrolled adults (average age or age range >36 and <60 years) [ 9 , 16 , 17 ], two enrolled older adults (average age or age range ≥60 years) [ 10 , 12 ] and one study reported an age range of 46-70 years [ 11 ]. Sample size ranged from 1-106 participants, with a median of 12 and a mean of 22 participants per study; 29 enrolled <30 [ 6 , 7 , 9 - 14 , 16 - 21 , 23 - 27 , 30 , 38 - 40 , 43 - 45 , 48 , 53 , 54 ] and 10 had ≥30 participants [ 22 , 31 , 33 , 36 , 37 , 41 , 47 , 49 , 52 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pundlik et al [104] did the secondary development for Google Glass to magnify the screen content of smartphone, thereby helping VIPs to easily access information displayed on the screen. They invited eight sighted and four VIP to employ calculator and music player apps on smartphone with the aid of proposed glass and built-in screen zoom app of phone.…”
Section: Vision Substitution By Assistive Glassesmentioning
confidence: 99%
“…Some recent examples have used consumer VR hardware: ForeSee [25] uses an Oculus Rift headset and IrisVision [29] uses a head-mounted smartphone (Samsung GearVR). Optical see-through displays have also been employed for vision enhancement [9,16], where virtual information is overlaid on a transparent display, thus augmenting rather than replacing the user's vision. For example, Google Glass has been used to display a magnified view of a smartphone screen [16] and to overlay enhanced edges onto the wearer's view of the real world [9]; however, Glass itself is a low-resolution display (640×360) and not designed as an AR device (e.g., the display is positioned in the user's visual periphery).…”
Section: Hmds To Enhance Vision Capabilitiesmentioning
confidence: 99%
“…For low vision users, headmounted displays (HMDs) that enhance a user's existing visual capabilities are particularly promising. For example, ForeSee [25] used an Oculus Rift VR headset with an attached camera to magnify and enhance text content, and other researchers have used Google Glass to enhance edges within the wearer's field of view [9] or display magnified content from a smartphone screen [16]. Several commercial HMDs (e.g., eSight [27], NuEyes [28], IrisVision [29]) display magnified video captured from a head-mounted camera, and provide image enhancement features such as contrast adjustment.…”
Section: Introductionmentioning
confidence: 99%